Faktor-Faktor Yang Mempengaruhi Pendapatan Pengusaha Industri Rumah Tangga Pengolahan Kue Kering di Kecamatan Banjarmasin Utara - Novendri , Risfy (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research is conducted to determine factors of initial capital, labor, raw materials, and working hours. Moreover, this research is conducted to determine which factor simultaneously affects the income and dominantly influences the pastry industry's payment in North Banjarmasin District. This research uses the quantitative method to obtain initial capital, labor, raw materials, and working hours. The data obtained using primary data is data directly taken from the source. This data is derived from questionnaires and direct interviews with the pastry industry owner in the District of North Banjarmasin. Based on the research, it was found that initial capital, labor, raw material, and working hours are the factors that affect the income of the pastry industry. Subsequently, the raw material is the dominant factor influencing the pastry industry's earnings in the District of North Banjarmasin.